If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + -12w = -2w + 75 Reorder the terms: 45 + -12w = 75 + -2w Solving 45 + -12w = 75 + -2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '2w' to each side of the equation. 45 + -12w + 2w = 75 + -2w + 2w Combine like terms: -12w + 2w = -10w 45 + -10w = 75 + -2w + 2w Combine like terms: -2w + 2w = 0 45 + -10w = 75 + 0 45 + -10w = 75 Add '-45' to each side of the equation. 45 + -45 + -10w = 75 + -45 Combine like terms: 45 + -45 = 0 0 + -10w = 75 + -45 -10w = 75 + -45 Combine like terms: 75 + -45 = 30 -10w = 30 Divide each side by '-10'. w = -3 Simplifying w = -3
| 4(x-4)+3=-5x+13 | | 3.4x+0.5=32.766 | | 6u^2+17u+15=0 | | -8x+9=-55 | | 3x+20=425 | | 396=22n | | 6x-1=9x-7 | | 10(v+4)-2v=2(4v+2)-5 | | 11-8p=-5 | | m=-0.50+50 | | 71+x=180 | | 2(v-6)-5v=3 | | 3+6s=4(s-3) | | 6(3x+7)=-4(-5x-7) | | x^2+1x-9=0 | | 4.3x+2.1x-2.3=7.6 | | r^3-11r^2-121r+1331= | | 96x^4+144x^2+51=0 | | x-0.2= | | (9+5i)+(11+2i)= | | 2x+40=6x+60 | | -3(y-2x)=5 | | 11+2z=14.75 | | 21x+24=20x+27 | | 2/3+w=1+1/2 | | 5(2s-1)=s+94 | | 5.952=0.992(-3.1+a) | | .2(10d+30)=13 | | F(x)=1x+-6 | | 80b+4680=58680 | | 3x-6=-3+4x | | 27(-0.7)= |